Acquisition of Sugar-Sweetened Beverages Among United States Households (OR16-03-19). (13th June 2019) - Onufrak, Stephen; Park, Sohyun; Pan, Liping; Lee, Seung Hee; Harris, Diane
Abstract: Objectives: Frequent consumption of sugar sweetened beverages (SSB) impacts diet quality and has been associated with obesity and type 2 diabetes. The purpose of this study was to assess SSB purchased or acquired for free by US households. This includes both SSB obtained and brought home (FAH) and SSB obtained for immediate consumption away from home (FAFH). Methods: We used data from the USDA Food Acquisition and Purchasing Survey (FoodAPS), which collected 7 days of data on all foods purchased or obtained for free in a nationally representative sample of 4826 households during 2012. Data was collected using food record books and bar code scanners. We assessed the prevalence of acquiring SSB during a given week, the amount of SSB calories acquired, money spent on SSB, and types of SSB acquired. We also examined differences in mean weekly household SSB calories by household size, region, and rural status using linear regression models with F tests to assess statistical significance. Results: During the one week study period, 77% of households acquired any SSB; 47% acquired SSB to bring home and 65% acquired SSB to consume away from home. Households had mean size of 2.4 members; they acquired an average of 1979 kcal of SSB per week and spent an average of $6.28 on SSB. More SSB calories were acquired to bring home (1223 kcal) than for away from home consumption (756 kcal). Soda was the leading type of SSB for at home (678 kcal) and away from home (472 kcal). Household SSB calories differed significantly by household size ( P  < 0.001) with each additional household member associated with a 735 kcal increase in household SSB kcal. Household SSB kcal differed by region ( P  = 0.02) and ranged from 1691 kcal in the Northeast to 2148 kcal in the South. Rural households had higher weekly SSB kcal compared to non-rural households (2255 kcal vs. 1838 kcal, P  = 0.03). Conclusions: This preliminary analyses suggests that U.S. households acquire nearly 2000 kcal of SSB per week. As more than 60% of SSB calories are acquired to bring home, efforts to improve diet quality among Americans could aim to reduce SSB acquisition for home consumption. Funding Sources: Funding is solely for staff time from internal Centers for Disease Control and Prevention funds.